Assessment on the measurement properties of the Brazilian Portuguese language version of the International Consultation on Incontinence Questionnaire Female Sexual Matters Associated with Lower Urinary Tract Symptoms Module (ICIQ-FLUTSsex) - Bruna Fonseca de Andrade; Leila Katz; Artur Eduardo de Oliveira Rangel; Julianna de Azevedo Guendler
Abstract Objectives: to assess internal consistency and reliability in providing a Portuguese version of the International Consultation on Incontinence Questionnaire Female Sexual Matters Associated with Lower Urinary Tract Symptoms Module (ICIQ-FLUTSsex). Methods: a validation study was conducted by applying questionnaires for 56 women over 18 years old with active sexual life and presenting urinary incontinence, excluding those who had urinary infection in the past 6 months. Three questionnaires were used, one for personal identification; the International Consultation on Incontinence Questionnaire - Short Form (ICIQ-SF) and the ICIQ-FLUTSsex. SPSS software was used for data analysis. Cronbach's alpha was used to verify reliability of the items on the questionnaires and Kappa coefficient was used to assess the agreement between the questionnaires applied in the test-retest. Results: the median age was 49.1 years old, mostly were mixed colored skin and married, with a high prevalence of mixed urinary incontinence. Cronbach's alpha score was 0.80, which was considered good. Kappa value was moderate, ranging from 0.36 to 0.76. Conclusion: internal consistency was considered good and reliability moderate. The Portuguese version of ICIQ-FLUTSsex was proven to be valid to use on women with urinary incontinence, contributing for clinical practice, as it provides as a quick tool for research on sexual dysfunction.